Genomic revelations: investigating rotavirus a presence in wild ruminants and its zoonotic potential - Šenica, Petra; Žele Vengušt, Diana; Vengušt, Gorazd; Kuhar, Urška (Frontiers in Veterinary Science, 2024)
Rotaviruses A (RVA) are a major cause of acute viral gastroenteritis in humans worldwide and are responsible for about two million hospitalisations per year. They can also infect other mammals such as pigs, calves, goats, lambs, and horses, in which they are also considered a major cause of viral diarrhoea. While RVA is well studied in humans and domestic animals, its occurrence in wild ruminants is not well known. The RVA genome is a double-stranded RNA consisting of 11 segments, and genotyping is based on the VP7 (G) and VP4 (P) segments. Currently, there are 42G genotypes and 58P genotypes. RVA has a high mutation rate, and some combinations of G and P genotypes can infect different animal species, leading to speculation about the potential for zoonotic transmission. 432 faecal samples were collected from roe deer, red deer, chamois, mouflon and Alpine ibex in Slovenia between 2017 and 2021. To investigate the presence of RVA in wild ruminants, real-time RT-PCR was used. Positive samples were subjected to next generation sequencing (NGS) using RIP-seq method. In total, 7 samples were RVA positive. Complete genomes were determined and phylogenetically analysed for all 7 RVAs. Four different genotype constellations were present in 7 positive RVA animals: G8-P[14]-I2-R2-C2-M2-A3-N2-T6-E2-H3, G6-P[14]-I2-R2-C2-M2-A11-N2-T6-E2-H3, G10-P[15]-I2-R2-C2-M2-A3-N2-T6-E2-H3 and G10-P[15]-I2-R2-C2-M2-A11-N2-T6-E2-H3. Genotypes G6P[14] and G10P[15] were found in both roe deer and red deer, representing the first confirmed occurrence of RVA in red deer. In addition, genotype G8P[14] was found in chamois, representing the first known case of positive RVA in this species. Some of these genotypes have also been found in humans, indicating the potential for zoonotic transmission.